0115 The Effect of Zolpidem on Sleep Dependent Emotional Memory Consolidation. (27th May 2020) - Simon, K C; Whitehurst, L; Zhang, J; Mednick, S
Abstract: Introduction: Psychopharmacological treatment is widely promoted for insomnia treatment. Zolpidem (ZOL) is a GABA A agonist that depresses the central nervous that has demonstrated unexpected benefits, specifically increased sleep-dependent verbal memory via increased phase-amplitude coupling between slow oscillations and sleep spindles (Niknazar et al., 2015). Here we investigated if ZOL improved sleep-dependent emotional memory consolidation. Methods: Using a within-subjects, cross-over design, we counterbalanced the administration of zolpidem (ZOL) or placebo (PBO) to 37 subjects in a double-blind study. Prior to drug or placebo administration, subjects rated their subjective physiological arousal of negative and neutral pictures. Subjects were tested on their recognition of the pictures twice, before (PM) and after (AM) a night of sleep. All subjects were monitored polysomnographically across the night. Results: We analyzed emotional picture recognition using 2-by-2 ANOVA (emotion x drug condition). We found a main effect of emotional picture PM performance, such that negative pictures were remembered better than neutral pictures. There was a significant main effect of sleep on AM false alarm rate, with greater false alarms for negative than neutral pictures, a significant interaction between drug and emotion on AM dprime, and a significant interaction for the difference between AM and PM performance and drug condition. Specifically, we found memory maintenance for both emotional picture types in ZOL but negative picture memory decline in PBO. Across the night, ZOL showed greater memory performance than PBO if subjects had greater N2 SWA and N2 sigma activity (12-15Hz). Conclusion: Zolpidem benefits sleep-dependent emotional memory consolidation by decreasing overnight forgetting. Further, it appears that spindle activity may play a key role in ZOL's memory effect. Support: NIH AG046646